Review Literatur: Faktor Resiko Depresi dan Kecemasan Pada Tenaga Kesehatan Selama Wabah COVID-19 - Esti Widiani; Lingling Marinda Palupi (Jurnal Kesehatan Andalas, 2022)
COVID-19 has created a state of anxiety and depression in health workers. Objectives: To identified what factors influence depression and anxiety. Methods: This literature summary used the PEOS framework. Search for articles through the ScienceDirect, PubMed, and Ovid databases in January 2021. The keywords used for the search for articles were (((((related factors) OR (risk factors)) AND (health workers)) OR (medical staff)) AND (anxiety)) AND (depression)) AND (covid 19). Results: The risk factors identified included age, gender, hours of work, front-line health workers, mental health, grade professional title, COVID-19 outbreak news or information, history of physical illness, negative experiences and social rejection, and fear of being exposed and transmitting COVID-19, and having children at home. Other risk factors included problems in the work environment, marital status, knowledge of COVID-19, quality of rest and sleep, living in the countryside, personal protective equipment, caring for family members, being infected with COVID-19, and bad family relationships. Many risk factors can trigger depression and anxiety. Conclusion:  Health policymakers must take steps to control these risk factors.Keywords:  depression; anxiety; COVID-19; healthcare worker